La pratique du nomadisme numérique par des salariés : enjeux sur la relation de travail - Catherine Minet-Letalle (Netcom)
Employees may wish to practice digital nomadism and thus work in different locations according to their migrations. While information and communication technologies make it possible today to work outside the company, it should not be forgotten that employees are under the legal subordination of their employer. They cannot therefore leave without a framework having been previously established with the employer, under penalty of being sanctioned by the latter. This framework is all the more important as frequent migrations of employees expose them to particular risks on their working conditions that must not be overlooked.